Characteristics of Cookies Using Brown Seaweed Flour (Turbinaria decurrens) and Chlorella vulgaris Flour as Functional Foods - Pitrianingsih, Santi; Pratama, Ginanjar; Meata, Bhatara Ayi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Cookies were made using mocaf flour and Turbinaria decurrens flour with the addition of Chlorella vulgaris flour. The purpose of this study was to determine the effect of different substitution ratios of Chlorella vulgaris flour, mocaf flour and Turbinaria decurrens flour on chemical and organoleptic characteristics, as well as its benefits as information in making functional food to meet daily nutritional needs. This study used an experimental method with a comparison of mocaf flour, Turbinaria decurrens flour, and Chlorella vulgaris flour consisting of 4 treatment levels, namely control (85%: 15%), C1 (84%: 15%: 1%), C2 (82%: 15%: 3%), and C3 (80%: 15%: 5%). The cookies acceptability test of the four formulas was conducted using the hedonic test. The selected formula was determined based on the preferences of 30 panelists. Based on the results of the study, it is known that cookies with treatment C1 with a ratio of mocaf flour: Turbinaria decurrens flour: Chlorella vulgaris flour (84%: 15%: 1%) is the best formula and contains 2.50% ash content, 39.22% fat content, 8.54 protein content. The most accepted by panelists is cookies with treatment C3 which has a moisture content of 3.40%, ash content of 2.76%, fat content of 42.36%, protein content of 6.62, and crude fiber of 6.75.